Th1 and Th2 cytokine response of peripheral blood macrophages-lymphocyte co-culture on challenge with Bacillus Calmette-Guérin and Mycobacterium tuberculosis H37RV in different categories of tuberculosis patients - Surangana Saha; Urmita Chakraborty; Avranil Goswami; Nishith Kumar Pal (Asian Journal of Medical Sciences, 2024)
Background: The quantitative analysis of Th1 and Th2 cytokines by in vitro challenged macrophages from tuberculosis (TB) patients of different clinical setting and healthy controls would enlighten our knowledge of macrophage efficiency at different ages and status of disease, facilitating new treatment feasibility by immunotherapy. Aims and Objectives: The aim of the study was to study the pattern of release of interferon-gamma (IFN-γ), interleukin-4 (IL-4), and IL-10 by macrophages, from pulmonary TB cases compared to normal individuals, in in vitro culture, on the challenge with Bacillus Calmette-Guérin (BCG) and Mycobacterium tuberculosis H37Rv. Materials and Methods: Fifteen sputum smear-positive newly diagnosed TB and 15 relapsed TB cases fulfilling the inclusion and exclusion criteria were recruited. Fifteen tuberculin skin test (TST) positive and 15 TST negative age- and sex-matched healthy volunteers were included as a control. Isolated macrophages were cultured and pretreated with BCG and H37Rv. After 24 h, the cell-free supernatant was collected and subjected to a sandwich enzyme-linked immunosorbent assay for IL-4, IL-10, and IFN-γ. Results: It was found that monocytes behave differently toward the virulent and avirulent strains of Mycobacterium in IFN-γ production. Th1 cytokine response was found to be higher by BCG challenge followed by H37Rv among all the study groups. However, Th2 cytokine responses with IL-10 and IL-4 were found to be higher in the patients as compared to healthy controls. Conclusion: Capacity to mount an inflammatory response determines the outcome of TB infection. Further study will enrich our knowledge in understanding the individual cell function and immunopathological mechanisms associated with the different clinical forms of TB.